Ultraviolet Photoprocessing of Glycine Adsorbed on Various Space-Relevant Minerals - Poggiali, Giovanni; Fornaro, Teresa; Potenti, Simone; Corazzi, Maria Angela; Brucato, John Robert (Frontiers in Astronomy and Space Sciences, 2020)
Mineral surfaces are energetic environments that can assist prebiotic organization by adsorbing selected molecules and allowing their concentration and chemical evolution, possibly toward complex (pre)biological systems. This dynamic rocky environment can also play a crucial role as promoters of chemical reactions towards increasing molecular complexity. Moreover, presence of minerals can mediate the effects of electromagnetic radiation and influence the photostability of biomolecules, catalyzing photoreaction or protecting molecules against degradation. Such interactions are responsible for the preservation/degradation mechanisms of organic molecules in space. In particular, the discovery of organic molecules on asteroids and comets confirms their role as transport and delivery vehicles of building blocks of life on Earth and possibly on other bodies of the Solar System, and the study of this kind of processes can improve our knowledge in astrobiology.Many different prebiotic and bio-molecules were detected in space and in meteorites, but among them amino acid glycine (H2NCH2COOH), is one of the most important. It is the simplest of the 20 biogenic amino acids and it is conceivably the link between complex organic molecules detected in our evolved Solar System and prebiotic molecules observed in the interstellar medium and protostellar environment. Laboratory simulations of UV processing may provide key insights into the survival of glycine and other biomarker in space environment, which is of particular relevance for upcoming space exploration missions on planetary surfaces, like ESA-Roscosmos ExoMars 2020, and sample return missions, like NASA OSIRIS-REx.We report a laboratory study of UV irradiation of glycine adsorbed on various space relevant minerals, i.e. forsterite, antigorite, spinel and pyrite, using a calibrated enhanced UV Xenon lamp, which demonstrated good performance as solar simulator. Comparing protective/catalytic effects of various minerals helps to unravel the role of rocky surfaces in the origin of life and provides hints for the search of organics in present and future robotic space exploration missions.